Penyelesaian Sistem Persamaan Non-Linier Dengan Metode Bisection & Metode Regula Falsi Menggunakan Bahasa Program Java - Endang Sunandar (PETIR, 2019)
The numerical method is a technique used to formulate mathematical problems so that they can be solved using ordinary arithmetic operations. In general, numerical methods are used to solve mathematical problems that cannot be solved by ordinary analytical methods. In the Numerical Method, we know two types of system equations, namely the Linear Equation System and the Non-Linear Equation System. Each system of equations has several methods. In the System, the Linear Equation between the methods is the Gauss Elimination method, the Gauss-Jordan Elimination method, the LU (Lower-Upper) Decomposition method. And for the Non-Linear Equation System between the methods is the Bisection method (Share-Two), Falsi Regula method, Newton Raphson method, Secant method, and Fix Iteration method. In this study, researchers are interested in comparing the two methods in the Non-Linear Equation System, namely the Bisection method and the Falsi Regula method. And this benchmarking process uses the Java programming language tool, this is to facilitate analysis of method completion algorithms, and monitoring in terms of execution time and output analysis. So that we can clearly know what differences occur between the two methods.